2004
DOI: 10.1111/j.1540-8159.2004.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Atrial Pacing Lead Implantation and Midterm Follow‐Up in Young Patients with Sinus Node Dysfunction After the Fontan Procedure

Abstract: The purpose of the study was to investigate the results of endocardial lead implantation, lead performance, and follow-up in young patients after the Fontan procedure. A retrospective study was conducted with patients who had endocardial atrial pacing for SND and intact AVN function after Fontan from two pediatric centers. Patient demographics, pacing, and sensing data of endocardial atrial leads were analyzed at the time of pacemaker implantation and follow-up visits. Fifteen patients (weight 42.6 +/- 35 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…A transvenous pacemaker approach has been utilized in a small number of patients with good short‐term follow‐up 25–27 . The major concern for the transvenous approach is the potential for clots to form around the pacing lead.…”
Section: Sinus Node Dysfunctionmentioning
confidence: 99%
“…A transvenous pacemaker approach has been utilized in a small number of patients with good short‐term follow‐up 25–27 . The major concern for the transvenous approach is the potential for clots to form around the pacing lead.…”
Section: Sinus Node Dysfunctionmentioning
confidence: 99%
“…Transvenous ventricular pacing can sometimes be accomplished with a lead advanced into a ventricular branch off the coronary sinus in patients with the old variety of atriopulmonary Fontan anastomosis, but this option is not available for those with modern cavopulmonary connections. 95,96 The venous route to the atrium and ventricle in Mustard or Senning patients is likewise challenging. Transvenous leads need to be advanced through the atrial baffle before fixation in the modified right atrium and the anatomic left ventricle, and it is not uncommon to encounter tight obstruction along the upper limb of the baffle that requires dilation and stent placement before leads can be passed.…”
Section: Lead Placementmentioning
confidence: 99%
“…Thirteen were anticoagulated or on antiplatelet medication. One of the two patients who were not on any anticoagulation or antiplatelet therapy had a transient ischemic attack during midterm follow‐up, which was felt to be related to a right to left shunt . Hansky et al reported seven patients after endocardial atrial pacing after the Fontan operation.…”
Section: Discussionmentioning
confidence: 99%